Les archives d’un prêtre savant à Istanbul : traces et supports mémoriels d’une communauté - Anna Théodoridès (Ateliers d'Anthropologie)
This article revisits a study of a Rûm Orthodox priest in Istanbul who, so as not to forget, assembles archives (in the form of eclectic collections of objects) of the history of the Rûm community, particularly of the pogrom of the night of 6-7 September 1955. The building of these collections is the result of an active effort to mobilise testimony and collect documentary evidence. Stored in his “loft”, a place of resistance and non-surrender, the objects are assembled according to a museum system, in which individual and collective memories are interconnected. This system is used as the basis of an analysis of how the priest builds these collections as a meaningful set of memory aids that are expected to become historical proofs.